Malati di SLA in Italia e meccanismi di diseguaglianza - Bosco, Nicoletta; Cappellato, Valeria (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
Despite the fact that guidelines on amyotrophic lateral sclerosis (Andersen et alii 2012, Ministero della Salute 2010) have established criteria to regulate health cures and organizational aspects, many mechanisms tending to produce or accentuate inequalities among patients can still be observed. The very choice of the category in which to fit them (people affected by rare disease, handicap, disability, non-self-sufficiency, chronic or terminal illness) is not to be overlooked, as it affects people’s rights and the institutional forms of support available to them. The following reflections are part of a wider research which, starting from the national legal framework, focused on the Piedmont region to investigate health care practices and problem areas. This research was carried out by analyzing secondary sources as well as 51 semi-structured interviews with privileged witnesses on a national level and participants involved in ALS interventions on a regional level.